2D speckle tracking echocardiography and comparison with cardiac magnetic resonance in children with acute myocarditis - Burešová, M.; Pavlíček, J.; Hanzlíková, P.; Tomášková, H.; Rybníček, O. (Frontiers in Cardiovascular Medicine, 2024)
Background: Cardiac magnetic resonance (CMR) plays a major diagnostic role in acute myocarditis (AM) in children as biopsy is rarely performed in this age group. Contribution of standard echocardiography (ECHO) is limited in AM, but speckle tracking echocardiography (STE) quantitatively characterizes myocardial function, with good sensitivity for detecting subclinical left ventricular (LV) dysfunction and regional kinetics disorders beyond the site of inflammation. This work aimed to evaluate the diagnostic potential of STE as compared with CMR findings in pediatric patients with AM.The study was conducted during 2022-2023. Troponin, electrocardiography, ECHO with STE, and CMR with early and late enhancement were performed on each patient. Affected heart segments were analyzed by both STE and CMR, and the correlation of the two methods was assessed.Results: During the study period, 20 children were diagnosed with AM (14 boys, 6 girls; mean age 12 years [median 14]). On ECHO, three patients had a deviation in LV biometry, and four patients had a mild systolic function disorder. STE showed at least one affected cardiac segment in all patients, most often the inferolateral segment (16/20; 80%). Of the 20 patients, STE showed a reduction in LV global longitudinal strain in 13 (65%) patients. In all patients, CMR identified an inflammatory focus, most frequently inferolateral (15/20; 75%). The strongest accordance between STE and CMR was observed for the involvement of anterolateral segments (k = 0.88) and the weakest for inferoseptal damage (k = 0.4).Conclusions: STE can provide important diagnostic information in pediatric patients with AM. This modality supports the detection of early regional edema and subclinical myocardial dysfunction and can determine the impairment severity. STE is non-invasive and repeatable without the need for special patient preparation or for general anesthesia.